Utilizing the Learning Health System Adaptation to guide Family Medicine Practice to COVID-19 response - Niharika Khanna; Elena N. Klyushnenkova; Alexander Kaysin; David L. Stewart (SAGE Publishing, 2020)
COVID-19 supportive quarantine care in the community is managed by primary care practices. There is no current guidance on how a primary care practice with high volumes of patients screened for COVID-19 can re-configure itself to become responsive to the pandemic. We examined Learning Health System guidance from the National Academies of Science, Engineering and Medicine and adapted it to our primary care practice to create an efficient, effective, adaptive response to the COVID-19 pandemic. We suggest evaluating this response in the future for effectiveness and efficiency.